IMF Staff papers : Volume 36 No. 4. (IMF Staff Papers; IMF Staff Papers, 1989)
Two recent criticisms of summary fiscal indicators are appraised: first, that they and the conventionally measured public sector balances from which they are derived are not sufficiently broadly defined; second, that they are meaningless because they do not reflect changes in the distribution of wealth between generations. The paper concludes that the defects of summary fiscal indicators have been exaggerated. It is not feasible to include all changes in public sector net worth in the deficit, and the existence of liquidity constraints and aversion to indebtedness imply that conventionally measured public sector deficits are not irrelevant.